ESTIMATION OF DIMETHOATE RESIDUE ON THE SURFACE OF MANGOES (Journal of Forensic Medicine & Toxicology, 2024)
Background: India is an agriculture-based country. The use of organophosphates is rampant for the protection of agricultural products from pests, during growing, storage and sometimes also for ripening. Exposure to pesticides can pose a potential risk to humans. These pesticides are widely used for the production of both vegetables and fruits. Dimethoate is one of the most common Organophosphorus (OP) pesticides sprayed on mangoes.
Keywords: Organophosphates; Dimethoate; High Performance Liquid Chromatography; Mango